P3.374 Treatment Failure Has Important Implications For Chlamydia Transmission and the Effectiveness of Screening Programmes. (13th July 2013) - Regan, D G; Wilson, D P; Hocking, J S
Abstract : Background: It is generally considered that current treatment regimens for chlamydia treatment are highly effective, achieving a cure rate of around 97%. Some recent studies, however, suggest that treatment failure may occur at a rate that is substantially higher than previously thought. Methods: We use a mathematical transmission model to estimate the population-level impact of treatment failure on chlamydia transmission and on the effectiveness of screening strategies in reducing chlamydia prevalence. We assume treatment failure rates ranging from 3% (baseline) to a maximum of 23% in the context of female-only and female-plus-male screening programmes where between 15% and 50% annual screening coverage is achieved. We examine the impact that increased treatment failure may have on prevalence and on the time and screening coverage required to achieve specific reductions in prevalence. Results: Based on sexual mixing patterns and health-seeking behaviour for young Australians, the model predicts that population prevalence would almost double, from ∼4.5% to ∼8%, if treatment failure increased from 3% to 23%. To compensate for higher assumed treatment failure, relative increases in screening coverage of between ∼4% and ∼16% will be required to achieve a reduction of 50% in chlamydia prevalence within 5 years under the treatment failure scenarios evaluated. The time required for screening to deliver equivalent reductions in prevalence as predicted under the baseline treatment failure rate is predicted to increase by between ∼6% and ∼35% (relatively) if the assumed treatment failure rate is increased to between 8% and 23%, depending on the screening strategy (female-only or female-plus-male) and the duration of screening (5 or 10 years). Conclusion: The rate of treatment failure may have a significant impact on the screening coverage and time required to achieve target reductions in chlamydia prevalence. This should be carefully considered when evaluating the potential effectiveness of proposed screening programmes.